DETERMINE PRE-ANALYTICAL ERRORS ’ PERCENTAGE IN CLINICAL BIOCHEMISTRY LABS AND DEVELOP REMEDIAL PROCEDURES FOR THEIR PREVENTION - NAWAZ , R; BASHIR , S; YASMEEN , S (Biological and Clinical Sciences Research Journal, 2023)
Diagnostic inaccuracies pose a formidable issue in Laboratory Medicine, necessitating immediate initiatives to expand understanding and minimize these discrepancies. Our study delves into the nuances of errors associated with laboratory testing processes, from the test request to result interpretation, underlining the imperative for reducing such errors. Our investigation seeks to identify the incidence of errors in a round-the-clock lab setting over four months, covering pre-analytical, analytical, and post-analytical phases.Over a span period from Jan 2021 to Jan 2022, a broad spectrum of errors within pre-analytical, analytical, and post-analytical phases was methodically logged using a bespoke proforma. The collected data was systematically analyzed utilizing SPSS version 22.All venous and arterial blood samples were processed in the 24-hour lab throughout this period. From the 185,012 samples received, 2,450 were deemed unsuitable for testing, accounting for a 1.32% rejection rate. These samples were disqualified due to an array of pre-analytical errors, including misidentification (0.07%), incorrect tube usage (0.11%), missing samples (0.07%), drawing from an intravenous site (0.10%), inadequate sample volume (0.51%), improper timing of sample collection (0.10%), hemolysed samples (0.31%), and lipemic samples (0.11%).Utilizing an agreed list of evidence-based Quality Indicators, compliant with the current International Standard (ISO 15189:2012), for incorporation into accreditation programs of clinical laboratories stands as a potent approach to augment quality, mitigate error risks, and bolster patient safety.